2017
DOI: 10.1021/acs.chemrev.7b00213
|View full text |Cite
|
Sign up to set email alerts
|

Soft X-ray Absorption Spectroscopy of Liquids and Solutions

Abstract: X-ray absorption spectroscopy (XAS) is an electronic absorption technique for which the initial state is a deeply buried core level. The photon energies corresponding to such transitions are governed primarily by the binding energies of the initial state. Because the binding energies of core electrons vary significantly among atomic species, this makes XAS an element-selective spectroscopy. Proper interpretation of XA spectra can provide detailed information on the local chemical and geometric environment of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
116
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(119 citation statements)
references
References 192 publications
(413 reference statements)
1
116
0
2
Order By: Relevance
“…Cations were found to order in the sequence Li + 4 Na + Z K + when considering the carbon K-edge, 12 yet as Na + 4 Li + 4 K + when targeting the oxygen K-edge, 11 with no apparent explanation for the discrepancy. 13 Polarizationresolved femtosecond mid-infrared spectroscopy, 14,15 has also been used to classify cations in the bulk by measuring the dynamics of slow-down water molecules in formate salts, resulting in the sequence Na + 4 Li + 4 K + 4 Cs + . On surfaces, vibrational sum frequency spectroscopy (VSFS) studies on fatty acid monolayers, concluded that K + binds more strongly than Na + , 16 while at relatively low concentrations (i.e., 1 mM salt) no discernible differences were reported between the monovalent cations with Li + E Na + E K + E Rb + .…”
Section: Introductionmentioning
confidence: 99%
“…Cations were found to order in the sequence Li + 4 Na + Z K + when considering the carbon K-edge, 12 yet as Na + 4 Li + 4 K + when targeting the oxygen K-edge, 11 with no apparent explanation for the discrepancy. 13 Polarizationresolved femtosecond mid-infrared spectroscopy, 14,15 has also been used to classify cations in the bulk by measuring the dynamics of slow-down water molecules in formate salts, resulting in the sequence Na + 4 Li + 4 K + 4 Cs + . On surfaces, vibrational sum frequency spectroscopy (VSFS) studies on fatty acid monolayers, concluded that K + binds more strongly than Na + , 16 while at relatively low concentrations (i.e., 1 mM salt) no discernible differences were reported between the monovalent cations with Li + E Na + E K + E Rb + .…”
Section: Introductionmentioning
confidence: 99%
“…1 XAS in the soft X-ray region has potentials to reveal hydrogen bond (HB) structures of liquid water and local structures of aqueous solutions, where solute organic molecules are measured in the C and N K-edges and solvent water is separately observed in the O K-edge. [2][3][4][5] It is also important that different functional groups with the same element such as the different sites of pyridine rings have been separately observed from the energy differences of XAS peaks. 6 However, soft X-rays are strongly absorbed by liquid and air.…”
Section: Soft X-ray Absorption Spectroscopy Of Liquids For Understandmentioning
confidence: 99%
“…In modern nanosciences, not only X-Ray Photoelectron Spectroscopy (XPS), but also advanced techniques such as Near-Edge X-Ray Absorption Fine Structure (NEXAFS) are important tools to study molecules in the gas phase as well as molecules or thin layers of molecules immobilized on a support. [1][2][3][4][5][6][7][8] Furthermore, dynamical systems such as liquids [9][10][11][12][13][14][15] and soft matter such as molecular crystals 16 , polymers 17,18 , and proteins 19 are objects of intense study, followed by the dynamics of material growth as for example graphene on copper 20 and oxidation processes of bulk condensed matter 21 . Always exciting a (core) electron in an energetically low-lying state through X-ray radiation, it is the energy and type of radiation that distinguishes different such spectroscopies.…”
Section: Introductionmentioning
confidence: 99%